Developing materials of listening comprehension for the English department students - Abdul Qodir; Luqman Baehaqi; M. Zaini Miftah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2016)
This study was designed to develop appropriate listening materials based on the needs of users namely the teachers and the students of the English Department of IAIN Palangka Raya. The Research and Development (R&D) design was applied in this study. The research subjects were four listening instructors and the first-semester students (freshmen) who encountered fourteen meetings of this on-going semester. The findings showed that (1) the stages of the listening materials development such as needs survey, developing materials, expert and instructors validation, revision, try out of materials, revision, and final product; (2) the product is in the form of compact disc recorded materials, an instructor’s guide, and a students’ worksheet; (3) the product consists of 14 units for semester 1; (4) the criteria for selecting materials are based on the existing syllabus and the criteria such as language, content, style of delivery, length, speed of delivery, attractiveness, practicality, level of difficulty and effectiveness; (5) the materials are appropriate for the students since they are relevant to the students’ need, interest, and level of students’ English ability; and (6) the listening activities can improve the students’ motivation to learn English.